Family and the television an audience study on the relationships and viewing habits of families - Emata, Sheila Marie P.
This study is all about the family and television. It is about how the relationship among family members affects their television viewing habits. The researcher studied three families. They were the Yaos, the Brennas and the Pablos and the Buros. The Yaos and the Brennas lived in Tondo, Manila. The Pablos and Buros lived in a house (making them one family) in Katipunan, Quezon City. The researcher spent seven days with each family. During her stay in their houses, she was able to observe their relationship with each other, their routines, their lifestyle and their television viewing habits. The researcher took note of the number of television sets that each family have. She also took note of the places where the televisions were located (living room, bedroom and kitchen). She also noted that the place where the television was located was also the place where the family gathered, a place where the family members were present for a time. The power structure or the hierarchy within the family was also observed during television watching. The dominant figure in the family could be seen through the member who decides what programs to watch at a certain time and sometimes by the person who holds the remote control.